2007
DOI: 10.1186/1744-9081-3-11
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: Craving for alcohol is a highly controversial subjective construct and may be clarified by Loewenstein's visceral theory, which emphasizes craving's behavioral effects on the relative value of alcohol. Based on the visceral theory, this study examined the effects of a craving induction on the relative value of alcohol as measured by a behavioral choice task. In addition, based on previous evidence of its role in the expression of craving, the influence of DRD4 VNTR genotype (DRD4-L vs. DRD4-S) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 94 publications
3
26
0
Order By: Relevance
“…The findings of the current study suggest cues influence demand and craving for IT. Although considering research on cue effects in the substance use disorder literature is still in infancy (Acker & MacKillop, 2013;Amlung et al, 2012;MacKillop, Menges, McGeary, & Lisman, 2007;MacKillop et al, 2010) and because this is currently the only study examining tanning demand and craving using a cue-reactivity paradigm, further research is necessary.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The findings of the current study suggest cues influence demand and craving for IT. Although considering research on cue effects in the substance use disorder literature is still in infancy (Acker & MacKillop, 2013;Amlung et al, 2012;MacKillop, Menges, McGeary, & Lisman, 2007;MacKillop et al, 2010) and because this is currently the only study examining tanning demand and craving using a cue-reactivity paradigm, further research is necessary.…”
Section: Discussionmentioning
confidence: 98%
“…Although HPTs are becoming increasingly popular in behavioral economic research on addictions (Bickel et al, 2011;Bickel et al, 2014;Jarmolowicz et al, 2016) and behavioral health in general , as of yet only one study has validated the TPT against two commonly used questionnaires in substance use disorder research. Given the growing number of validation studies in the substance use literature (e.g., alcohol and tobacco; Amlung et al, 2012;Amlung & MacKillop, 2014;Amlung et al, 2015;MacKillop et al, 2007;MacKillop & Lisman, 2008;MacKillop et al, 2010;Madden & Kalman, 2010), future research may attempt to validate the TPT with tanning specific addiction tools such as the Structured Interview for Tanning Abuse and Dependence (Hillhouse, Baker, Turrisi, Shields, Stapleton, Jain, & Longacre, 2012), the Tanning Pathology Scale (Heckman et al, 2014;Hillhouse et al, 2010), and experiential tasks.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, performance for hypothetical alcohol has been shown to be highly correlated with performance for actual alcohol (Amlung et al, 2012). In addition, state-oriented purchase tasks capture cue-elicited increases in motivation for alcohol (MacKillop et al, 2010b, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…These variants were identified as potential genetic risk factors for cue-induced drug craving and subsequent relapse to substance use. Though other findings relating DRD4 VNTR allele and cue reactivity have been contradictory (MacKillop et al, 2007; van den Wildenberg et al, 2007), Hutchison et al (2002) found an association between this allele with greater cue-induced craving and arousal among smokers.…”
Section: Pharmacogenetics Of Drug Effects and Treatment Outcomementioning
confidence: 85%